2019
DOI: 10.1080/23802359.2019.1674729
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of Platencyrtus parkeri Feriere (Hymenoptera: Encyrtidae)

Abstract: The mitochondrial genome of the Platencyrtus parkeri Feriere (Hymenoptera: Encyrtidae) was obtained via next-generation sequencing. The assembled mitogenome is 13,393 bp in length, which contains 33 classical eukaryotic mitochondrial genes with three tRNA genes and rrnS gene missing. All the 13 PCGs begin with typical ATN codons. The 19 detected tRNAs range from 58 to 70 bp in length with typical cloverleaf structure except for trnS1, whose dihydrouridine (DHU) arm forms a simple loop. Meanwhile, they have six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…To validate the above conjecture, we examined the spacing and overlap patterns of the identified genes within the mitochondrial genome of Encyrtidae, and the results indicated that E. philippinensis is similar to other Encyrtidae members in relation to gene organization and composition (Zhang et al. 2019 ; Zhou et al. 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…To validate the above conjecture, we examined the spacing and overlap patterns of the identified genes within the mitochondrial genome of Encyrtidae, and the results indicated that E. philippinensis is similar to other Encyrtidae members in relation to gene organization and composition (Zhang et al. 2019 ; Zhou et al. 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…Pteromalidae has been considered as a polyphyletic group for decades [17]. This concept was supported by several studies [18][19][20], even though Pteromalidae was recovered as monophyletic in several other studies [16,21,22]. Rasplus et al [23] suggested that Sycoecinae, Otitesellinae, and Sycoryctinae (used to be Agaonidae) should be transferred to Pteromalidae based on ribosomal and mitochondrial genes as well as morphology.…”
Section: Introductionmentioning
confidence: 97%